Method for testing sintering performance of metal fine powder

By mixing the metal fine powder with coarse powder in proportion and performing sintering tests, the problems of poor fluidity and serious agglomeration of fine powder are solved, and the accurate evaluation and improvement of the sintering performance of fine powder is achieved.

CN119595455APending Publication Date: 2025-03-11SUZHOU CUBRAZING MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411830989.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The prior art is difficult to accurately evaluate the sintering performance of metal fine powders, especially when the fine powder is small in size, poor fluidity and serious agglomeration, resulting in defects in the sintered body and affecting mechanical properties.

Method used

By mixing the metal fine powder with metal coarse powder with larger particle size in a certain proportion, the fine powder is evenly coated on the surface of the coarse powder, and the bending strength of the sintered body is tested through the compaction and sintering process to calculate the relative sintering index to evaluate the sintering performance of the fine powder.

Benefits of technology

The fluidity and sintering defects of fine powder are improved, and the microscopic characteristics of fine powder are ensured. At the same time, through scientific and objective evaluation methods, the performance of the powder during the sintering process is accurately reflected.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119595455A_ABST
    Figure CN119595455A_ABST
Patent Text Reader

Abstract

The invention discloses a metal fine powder sintering performance testing method which comprises the following steps: mixing metal fine powder and metal coarse powder according to a ratio, and coating the metal fine powder on the outer surface of the metal coarse powder to obtain mixed powder; the mixed powder and the metal coarse powder are put into a mold to be compacted through vibration and then sintered, and a mixed powder sintered body and a metal coarse powder sintered body are obtained; and the bending strength A of the mixed powder sintered body and the bending strength B of the metal coarse powder sintered body are tested, the relative sintering index A / B of the mixed powder and the metal coarse powder is calculated, and the sintering performance of the metal fine powder is represented through the relative sintering index A / B. According to the method for testing the sintering performance of the metal fine powder, through the combination mode of the fine powder and the coarse powder, the problems of poor fluidity and serious agglomeration possibly occurring when the fine powder is independently used are solved, and the sintering performance of the fine powder is objectively evaluated; therefore, the performance of the fine powder in the sintering process can be evaluated more accurately.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal powder performance testing, and in particular relates to a method for testing the sintering performance of metal fine powder. Background Art

[0002] During the sintering process of metal powder, the particle size has a significant impact on the sintering performance. As the particle size of metal powder decreases, the surface energy and adsorption force between powder particles increase significantly, resulting in a gradual decrease in powder fluidity. Metal powder with a smaller particle size is prone to agglomeration and accumulation during processing, which has a serious impact on the uniform mixing and sintering performance of the powder.

[0003] At present, the evaluation of the sintering performance of metal powders mainly relies on testing the physical and mechanical properties after sintering. Common sintering methods include powder compacting sintering and vibration sintering. Powder compacting sintering is to press the powder into blocks and then heat them for sintering. However, due to the poor fluidity of metal fine powders, it is difficult to achieve uniform rearrangement during pressing, resulting in large gaps and cracks between particles.

[0004] Vibration sintering is to load powder into a mold and promote the rearrangement of powder by vibration. However, vibration sintering also faces the strong surface adsorption between micron and submicron powders. This strong adsorption makes it easy for powder to agglomerate during the vibration process, resulting in insufficient rearrangement of powder. Bridging and voids still exist in the sintered structure. These defects directly affect the mechanical properties of the sintered body, making it difficult to accurately evaluate the sintering performance of the powder through the sintered body.

[0005] Therefore, it is necessary to provide a new solution to the above technical problems. Summary of the invention

[0006] The object of the present invention is to provide a method for testing the sintering performance of metal fine powders, which can more accurately evaluate the sintering performance differences between different metal fine powders.

[0007] To achieve the above purpose, the technical solution provided by the present invention is as follows:

[0008] In a first aspect, the present invention provides a method for testing the sintering performance of metal fine powder, wherein the particle size of the metal fine powder is 0.1 to 10 μm, and the method comprises:

[0009] A metal fine powder and a metal coarse powder with a particle size of 30 to 100 μm are mixed in proportion so that the metal fine powder is evenly coated on the outer surface of the metal coarse powder to obtain a mixed powder; the mixed powder and the metal coarse powder are respectively loaded into molds of the same specifications and compacted, and then sintered under the same conditions to obtain a mixed powder sintered body and a metal coarse powder sintered body; the flexural strength A of the mixed powder sintered body and the flexural strength B of the metal coarse powder sintered body are tested, and the relative sintering index A / B of the mixed powder and the metal coarse powder is calculated, and the sintering performance of the metal fine powder is characterized by the relative sintering index A / B.

[0010] In one or more embodiments, the mass ratio of the metal fine powder to the metal coarse powder is 1:(1-3).

[0011] In one or more embodiments, the mixing method of the metal fine powder and the metal coarse powder includes: mixing the metal fine powder and the metal coarse powder, adding a wetting agent, and mixing them in a mixer.

[0012] In one or more embodiments, the wetting agent includes at least one of paraffin, glycerin, and spindle oil.

[0013] In one or more embodiments, the amount of the wetting agent added is 0.2-0.5% of the total mass of the metal fine powder and the metal coarse powder.

[0014] In one or more embodiments, before mixing the metal fine powder and the metal coarse powder, the metal coarse powder is subjected to plasma treatment to increase the surface energy of the metal coarse powder.

[0015] In one or more embodiments, the plasma treatment method includes: placing the metal coarse powder into a plasma reactor, using oxygen as a plasma source, and processing for 3 to 5 minutes under the conditions of an operating pressure of 100 Pa and a radio frequency power of 200 W.

[0016] In one or more embodiments, the sintering method of the mixed powder and the metal coarse powder includes: placing a mold containing the mixed powder and the metal coarse powder into a sintering furnace, and sintering at 600-930° C. for 50-80 minutes in a reducing atmosphere or a protective atmosphere.

[0017] In one or more embodiments, the reducing atmosphere is a hydrogen atmosphere or an ammonia decomposition atmosphere.

[0018] In one or more embodiments, the metal fine powder is a single substance powder such as copper powder or an alloy powder such as steel powder.

[0019] Compared with the prior art, the method for testing the sintering performance of metal fine powder provided by the present invention improves the fluidity and sintering defects of fine powder by combining fine powder and coarse powder, so that the fine powder is evenly coated on the surface of coarse powder, which not only maintains the microscopic characteristics of the fine powder, but also can utilize the relatively large particle size and lower surface energy of the coarse powder, avoiding the problems of poor fluidity and severe agglomeration that may occur when the fine powder is used alone; at the same time, by sintering the mixed powder and testing the flexural strength of the sintered body, and by introducing the flexural strength as a quantitative indicator, the sintering performance of the fine powder can be scientifically and objectively evaluated; thereby, the performance of the powder during the sintering process can be more accurately evaluated. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0021] Figure 1 This is a flow chart of a method for testing the sintering performance of metal fine powder in one embodiment of the present invention;

[0022] Figure 2 This is a scanning electron microscope image of a sintered body of a reference example of the present invention;

[0023] Figure 3 This is a scanning electron microscope image of the sintered body of Example 1 of the present invention;

[0024] Figure 4 is a scanning electron microscope image of the sintered body of Example 2 of the present invention;

[0025] Figure 5 is a scanning electron microscope image of the sintered body of Example 4 of the present invention;

[0026] Figure 6 This is a scanning electron microscope image of the sintered body of Example 5 of the present invention;

[0027] Figure 7 This is a scanning electron microscope image of the sintered body of Example 6 of the present invention;

[0028] Figure 8 This is a scanning electron microscope image of the sintered body of Example 7 of the present invention. DETAILED DESCRIPTION

[0029] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0030] It should be noted that in the following description, the "%" indicating the amount is a weight basis unless otherwise specified. Unless otherwise specified, all numbers used in this specification and claims to indicate characteristic dimensions, quantities and physical properties should be understood to be modified by the term "about" in all cases. Therefore, unless otherwise specified, the numerical parameters listed in the above specification and the attached claims are approximate values, and those skilled in the art can use the teachings disclosed herein to seek to obtain the desired properties and appropriately change these approximate values. The use of numerical ranges expressed as endpoints includes all numbers within the range and any range within the range, for example, 1 to 5 includes 1, 1.2, 1.4, 1.55, 2, 2.75, 3, 3.80, 4 and 5, etc.

[0031] With the continuous development of materials science and powder metallurgy technology, the sintering performance evaluation of metal powders has become a key link in improving manufacturing accuracy and product performance. However, with the continuous reduction of powder particle size, especially the widespread application of micron- to nano-scale metal fine powders, the fluidity and sintering problems of powders have become increasingly prominent, especially in the sintering process of fine powders, there are problems such as agglomeration, stratification, and poor fluidity, which makes it difficult for traditional sintering performance evaluation methods to accurately reflect the true sintering performance of powders.

[0032] Among the existing sintering methods, the commonly used powder compact sintering and vibration sintering methods can evaluate the sintering performance of powders. However, due to the small particle size of fine powders and their high surface energy, adsorption and agglomeration between powder particles are easy to occur, resulting in more defects in the sintered body and unstable sintering process, which ultimately affects the density and mechanical properties of the sintered body. These problems make it difficult to obtain reliable evaluation results during the fine powder sintering process.

[0033] Based on this, the inventors have come up with ideas for improvement from the shortcomings of the prior art. The inventors believe that the fundamental reason for the poor fluidity and serious agglomeration of fine powders is that the powders have small particle sizes and large surface energy, which leads to strong adsorption between particles and agglomeration that is difficult to break up. Therefore, how to improve the fluidity and reduce agglomeration without changing the basic physical properties of the powder has become the core issue of the present invention.

[0034] The present invention proposes a method for testing the sintering performance of metal fine powder, which aims to improve the fluidity and sintering defects of fine powder by combining fine powder and coarse powder. In this method, metal fine powder and metal coarse powder are mixed in a certain proportion, and the fine powder is evenly coated on the surface of the coarse powder. This not only maintains the microscopic characteristics of the fine powder, but also can utilize the relatively large particle size and low surface energy of the coarse powder, avoiding the problems of poor fluidity and severe agglomeration that may occur when fine powder is used alone. At the same time, by sintering the mixed powder and testing the flexural strength of the sintered body, and by introducing the flexural strength as a quantitative indicator, the sintering performance of the fine powder can be scientifically and objectively evaluated; thereby being able to more accurately evaluate the performance of the powder during the sintering process.

[0035] Please refer to Figure 1 The figure is a flow chart of a method for testing the sintering performance of metal fine powder in one embodiment of the present invention. The method for testing the sintering performance of metal fine powder is suitable for testing the sintering performance of metal fine powder with a particle size of 0.1 to 10 μm. The method specifically comprises the following steps:

[0036] S101: Mix metal fine powder and metal coarse powder with a particle size of 30 to 100 μm in proportion, so that the metal fine powder is evenly coated on the outer surface of the metal coarse powder to obtain a mixed powder.

[0037] Specifically, the mass ratio of metal fine powder to metal coarse powder is 1:(1-3). If the proportion of fine powder is too high, it may lead to poor fluidity of the mixed powder, unstable sintering process, and even agglomeration of fine powder during sintering, thereby affecting the quality of the sintered body. By setting the mass ratio of 1:(1-3), it can be ensured that the fine powder will not excessively affect the fluidity of the mixed powder and the smooth progress of the sintering process while ensuring a good coating effect.

[0038] In an exemplary embodiment, the method of mixing the metal fine powder and the metal coarse powder includes: mixing the metal fine powder and the metal coarse powder, adding a wetting agent, and mixing them in a mixer.

[0039] In the specific implementation process, the metal fine powder and the metal coarse powder are weighed according to the required proportion and put into the mixer. In order to make the fine powder evenly coated on the surface of the coarse powder, a wetting agent is added. The function of the wetting agent is to reduce the electrostatic adsorption between the powders, improve the fluidity of the powders, and prevent the fine powder from agglomerating or agglomerating during the mixing process. The wetting agent changes the wettability of the powder surface, so that the fine powder can better contact with the coarse powder surface, and helps the uniform coating between the fine powder and the coarse powder.

[0040] Specifically, the wetting agent includes at least one of paraffin, glycerin and spindle oil. The amount of the wetting agent added is 0.2-0.5% of the total mass of the metal fine powder and the metal coarse powder.

[0041] Wetting agents can reduce the friction and adsorption between powders, enhance the compatibility of fine powder and coarse powder, prevent powder agglomeration during mixing, and ensure the uniformity and fluidity of the mixture. Paraffin, glycerin and spindle oil all have strong lubricity and surface activity, which can reduce the electrostatic adsorption between powders and prevent powder agglomeration or agglomeration. Paraffin has a low viscosity and can form a uniform film, which helps to improve the fluidity and dispersibility of powders; glycerin has a low surface tension, which can effectively reduce the friction between powders and has a certain wetting effect on the surface of metal powders; spindle oil has good lubricity and volatility, which can effectively reduce the adhesion and friction between powders.

[0042] In an exemplary embodiment, before mixing the metal fine powder and the metal coarse powder, the metal coarse powder is subjected to plasma treatment to increase the surface energy of the metal coarse powder.

[0043] Plasma treatment is a surface modification technology that changes the surface properties of materials, especially surface energy and chemical activity, by acting on the surface of materials in a low-temperature plasma environment. For metal powders, plasma treatment can increase their surface activity, thereby affecting the interaction between powders.

[0044] Plasma treatment can effectively remove the oxide layer and other contaminants on the surface of the coarse powder, which will affect the surface characteristics of the metal powder and make it difficult for the fine powder to be evenly distributed during the mixing process. By removing these unfavorable factors, the surface of the coarse powder becomes more active, providing better conditions for the coating of the fine powder. In addition, the increased surface energy helps the interaction between the fine powder and the coarse powder, especially enhancing the adhesion of the fine powder on the surface of the coarse powder, so that the metal fine powder can be more evenly coated on the outer surface of the coarse powder.

[0045] Specifically, the plasma treatment method includes: placing the metal coarse powder into a plasma reactor, using oxygen as a plasma source, and processing for 3 to 5 minutes under the conditions of an operating pressure of 100 Pa and a radio frequency power of 200 W.

[0046] Plasma reactors generate plasma by applying high voltage or radio frequency power to ionize gas, which contains high-energy electrons, ions, free radicals and other particles. The purpose of choosing oxygen as the plasma source is that oxygen can produce active oxygen species with strong oxidizing properties in the plasma state. These active oxygen species can clean the surface of the metal coarse powder, remove the oxide layer, oil stains, etc., and increase the chemical activity of the metal coarse powder surface.

[0047] In actual operation, the pressure in the reactor is set to 100Pa and the RF power is set to 200W. The low-pressure environment is conducive to the generation of high-energy plasma, and the RF power is controlled at 200W to ensure the activity and uniformity of the plasma, thereby efficiently treating the surface of the metal coarse powder. The treatment time is set to 3 to 5 minutes to ensure that the surface of the metal coarse powder is fully modified while avoiding surface damage caused by excessive treatment.

[0048] S102: The mixed powder and the metal coarse powder are respectively loaded into molds of the same specifications, compacted by vibration, and then sintered under the same conditions to obtain a mixed powder sintered body and a metal coarse powder sintered body.

[0049] The purpose of step S102 is to ensure that the two powders undergo the same physical treatment under the same sintering conditions, so that the different characteristics they exhibit during the sintering process can be compared later, and the sintering performance of the metal fine powder can be evaluated.

[0050] The mixed powder and the metal coarse powder need to be loaded into molds of the same specifications to ensure that they are subject to the same external environment and processing conditions during the sintering process. The specifications of the mold must ensure that the shape and size of the sintered body are consistent to avoid incomparable sintering results due to mold differences.

[0051] The mixed powder and the coarse metal powder are vibrated separately. The purpose of vibration is to remove the pores that may be generated in the powder during the mold filling process, increase the density of the powder, and ensure that it can obtain better physical contact and reaction during the sintering process, so as to obtain higher sintering quality. The vibration method usually uses a vibration table or other special equipment to vibrate the powder at a certain frequency and amplitude to fully align it and remove the air, further optimizing the bonding effect between the powders.

[0052] After the compaction, the powder samples are sintered under the same sintering conditions. Sintering is the process of heating the powder to diffuse and form solid connections between the particles. Factors such as sintering temperature, atmosphere and time have an important influence on the performance of the final sintered body. Therefore, in the sintering step, it is necessary to ensure that the two powders are sintered under the same conditions to ensure that the test results are comparable.

[0053] In an exemplary embodiment, the sintering method of the mixed powder and the metal coarse powder includes: placing the mold containing the mixed powder and the metal coarse powder into a sintering furnace, and sintering at 600-930° C. for 50-80 minutes in a reducing atmosphere or a protective atmosphere. The reducing atmosphere is a hydrogen atmosphere or an ammonia decomposition atmosphere.

[0054] The sintering temperature is selected in the range of 600-930°C. This temperature range can effectively promote the sintering reaction of metal powder (such as copper powder). At a lower temperature, the diffusion rate between powder particles is slower and the density of the sintered body is lower, but too high a temperature may cause excessive melting of the powder or morphological changes. Therefore, 600-930°C is an ideal sintering temperature range. The specific temperature selection can be adjusted according to the type and size of the powder used and the required properties of the sintered body. For example, a temperature of about 600°C can effectively sinter copper powder.

[0055] The reducing atmosphere is mainly to prevent oxidation of the powder surface and promote diffusion between metal powders. Here, hydrogen atmosphere or ammonia decomposition atmosphere is a commonly used reducing atmosphere. Hydrogen has strong reducing properties and can effectively remove the oxide layer on the powder surface and promote diffusion and bonding between particles. The combined effect of nitrogen and hydrogen in the ammonia decomposition atmosphere also has a reducing effect, which can maintain the purity of the sintered body and avoid the formation of impurities. These atmospheres help to improve the contact performance of metal particles and promote bonding and sintering between powder particles.

[0056] At the beginning of sintering, the mixed powder is heated to a high temperature area, and the fine powder and coarse powder particles begin to contact. Since the metal fine powder is coated on the outer surface of the coarse powder, this structure causes the fine powder to become the main participant in the sintering process. During the heating process, the fine powder particles first absorb heat and heat up, gradually reaching or exceeding their melting point, while the coarse powder particles remain in a more stable state at a higher temperature because of their larger particle size and relatively slower heating rate.

[0057] As the temperature rises, the surface of the fine powder particles begins to melt and form a liquid phase, while the coarse powder particles, due to their larger size and higher melting temperature, do not melt completely at first and usually appear as solid phase particles. During the sintering process, the surface of the fine powder particles begins to soften and fuse with the surface of the coarse powder particles. This process is mainly the welding and diffusion between fine powder and fine powder, and between fine powder and coarse powder.

[0058] During the sintering process, as the temperature rises further, more fine powder particles fuse to the surface of coarse powder particles, increasing the contact area between the particles and making the connection tighter. In this process, the interface between fine powder and coarse powder gradually disappears, forming a more uniform sintered body structure.

[0059] S103: testing the flexural strength A of the mixed powder sintered body and the flexural strength B of the metal coarse powder sintered body, calculating the relative sintering index A / B of the mixed powder and the metal coarse powder, and using the relative sintering index A / B to characterize the sintering performance of the metal fine powder.

[0060] The sintering performance of metal fine powder is characterized by testing the flexural strength A of the mixed powder sintered body and the flexural strength B of the metal coarse powder sintered body, and then calculating the relative sintering index A / B of the two. By comparing the mechanical properties of different sintered bodies, the performance of metal fine powder during the sintering process is indirectly evaluated, thereby obtaining a quantitative and comparable sintering performance index to evaluate the sintering performance differences of different metal fine powders.

[0061] In the present invention, the bending strength of the mixed powder sintered body and the metal coarse powder sintered body is tested, the purpose is to reveal the sintering effect of the metal fine powder by comparing their mechanical properties. The relative sintering index A / B is a dimensionless ratio, which provides a quantitative evaluation standard for the sintering performance of the metal fine powder by comparing the strength difference of the two different powder sintered bodies. Through this index, the sintering effect of the metal fine powder can be effectively measured. For example, if the sintered body of the mixed powder is better than the sintered body of the metal coarse powder, that is, A / B is greater than 1, then it means that the sintering performance of the fine powder is better and can promote the bonding between particles during the sintering process.

[0062] The present invention will be further described below in conjunction with specific embodiments.

[0063] Benchmark Example

[0064] After copper powder with a particle size of 50 μm is put into a mold and compacted, it is placed in a brazing furnace, the sintering temperature is set to 600°C, sintering is performed in an ammonia decomposition atmosphere, and the high-temperature sintering time is maintained for 70 minutes. After sintering, the sintered body is naturally cooled to room temperature, and the flexural strength B of the sintered body is tested, and the flexural strength B is used as the benchmark strength. Figure 2 This is a scanning electron microscope image of the sintered body of the reference example.

[0065] Example 1

[0066] Copper powder with a particle size of 50 μm and copper powder with a particle size of 4 μm were mixed in a mass ratio of 1:1. During the mixing process, 0.3% of spindle oil of the total powder mass was added as a wetting agent. The mixture was placed in a W-100 double cone mixer and mixed for 20 minutes to ensure that the fine copper powder was evenly coated on the surface of the coarse copper powder.

[0067] The mixed powder was placed in a mold and compacted, then placed in a brazing furnace, the sintering temperature was set to 600°C, sintered in an ammonia decomposition atmosphere, and the high temperature sintering time was maintained for 70 minutes. After sintering, the sintered body was naturally cooled to room temperature, and the bending strength of the sintered body was tested. Figure 3 This is a scanning electron microscope image of the sintered body of Example 1.

[0068] Example 2

[0069] Copper powder with a particle size of 50 μm and copper powder with a particle size of 2 μm were mixed in a mass ratio of 1:1. During the mixing process, 0.3% of spindle oil of the total powder mass was added as a wetting agent. The mixture was placed in a W-100 double cone mixer and mixed for 20 minutes to ensure that the fine copper powder was evenly coated on the surface of the coarse copper powder.

[0070] The mixed powder was placed in a mold and compacted, then placed in a brazing furnace, the sintering temperature was set to 600°C, sintered in an ammonia decomposition atmosphere, and the high temperature sintering time was maintained for 70 minutes. After sintering, the sintered body was naturally cooled to room temperature, and the bending strength of the sintered body was tested. Figure 4 This is a scanning electron microscope image of the sintered body of Example 2.

[0071] Example 3

[0072] Copper powder with a particle size of 50 μm and copper powder with a particle size of 1 μm were mixed in a mass ratio of 1:1. During the mixing process, 0.3% of spindle oil of the total powder mass was added as a wetting agent. The mixture was placed in a W-100 double cone mixer and mixed for 20 minutes to ensure that the fine copper powder was evenly coated on the surface of the coarse copper powder.

[0073] The mixed powder was placed in a mold and compacted, then placed in a brazing furnace, the sintering temperature was set to 600°C, sintered in an ammonia decomposition atmosphere, and the high temperature sintering time was maintained for 70 minutes. After sintering, the sintered body was naturally cooled to room temperature, and the bending strength of the sintered body was tested.

[0074] Example 4

[0075] Copper powder with a particle size of 50 μm and copper powder with a particle size of 4 μm were mixed in a mass ratio of 3:1. During the mixing process, 0.3% of spindle oil of the total powder mass was added as a wetting agent. The mixture was placed in a W-100 double cone mixer and mixed for 20 minutes to ensure that the fine copper powder was evenly coated on the surface of the coarse copper powder.

[0076] The mixed powder was placed in a mold and compacted, then placed in a brazing furnace, the sintering temperature was set to 600°C, sintered in an ammonia decomposition atmosphere, and the high temperature sintering time was maintained for 70 minutes. After sintering, the sintered body was naturally cooled to room temperature, and the bending strength of the sintered body was tested. Figure 5 This is a scanning electron microscope image of the sintered body of Example 4.

[0077] Example 5

[0078] Copper powder with a particle size of 50 μm and copper powder with a particle size of 2 μm were mixed in a mass ratio of 3:1. During the mixing process, 0.3% of spindle oil of the total powder mass was added as a wetting agent. The mixture was placed in a W-100 double cone mixer and mixed for 20 minutes to ensure that the fine copper powder was evenly coated on the surface of the coarse copper powder.

[0079] The mixed powder was placed in a mold and compacted, then placed in a brazing furnace, the sintering temperature was set to 600°C, sintered in an ammonia decomposition atmosphere, and the high temperature sintering time was maintained for 70 minutes. After sintering, the sintered body was naturally cooled to room temperature, and the bending strength of the sintered body was tested. Figure 6 This is a scanning electron microscope image of the sintered body of Example 5.

[0080] Example 6

[0081] Copper powder with a particle size of 50 μm and copper powder with a particle size of 1 μm were mixed in a mass ratio of 3:1. During the mixing process, 0.3% of spindle oil of the total powder mass was added as a wetting agent. The mixture was placed in a W-100 double cone mixer and mixed for 20 minutes to ensure that the fine copper powder was evenly coated on the surface of the coarse copper powder.

[0082] The mixed powder was placed in a mold and compacted, then placed in a brazing furnace, the sintering temperature was set to 600°C, sintered in an ammonia decomposition atmosphere, and the high temperature sintering time was maintained for 70 minutes. After sintering, the sintered body was naturally cooled to room temperature, and the bending strength of the sintered body was tested. Figure 7 This is a scanning electron microscope image of the sintered body of Example 6.

[0083] Example 7

[0084] Copper powder with a particle size of 50 μm was placed in a plasma reactor, with oxygen as the plasma source, under the conditions of an operating pressure of 100 Pa and a radio frequency power of 200 W, the treatment time was 5 min.

[0085] The plasma-treated copper powder and the copper powder with a particle size of 4 μm were mixed in a mass ratio of 1:1. During the mixing process, 0.3% of spindle oil of the total powder mass was added as a wetting agent. The mixture was placed in a W-100 double cone mixer and mixed for 20 minutes to ensure that the fine copper powder was evenly coated on the surface of the coarse copper powder.

[0086] The mixed powder was placed in a mold and compacted, then placed in a brazing furnace, the sintering temperature was set to 600°C, sintered in an ammonia decomposition atmosphere, and the high temperature sintering time was maintained for 70 minutes. After sintering, the sintered body was naturally cooled to room temperature, and the bending strength of the sintered body was tested. Figure 8 This is a scanning electron microscope image of the sintered body of Example 7.

[0087] Comparative Example 1

[0088] After copper powder with a particle size of 4 μm is put into a mold and compacted, it is placed in a brazing furnace, the sintering temperature is set to 600°C, sintering is carried out in an ammonia decomposition atmosphere, and the high temperature sintering time is maintained for 70 minutes. After sintering, the sintered body is naturally cooled to room temperature, and the bending strength of the sintered body is tested.

[0089] Comparative Example 2

[0090] After copper powder with a particle size of 2 μm is put into a mold and compacted, it is placed in a brazing furnace, the sintering temperature is set to 600°C, sintering is carried out in an ammonia decomposition atmosphere, and the high temperature sintering time is maintained for 70 minutes. After sintering, the sintered body is naturally cooled to room temperature, and the bending strength of the sintered body is tested.

[0091] Comparative Example 3

[0092] After the copper powder with a particle size of 1 μm is put into the mold and compacted, it is placed in the brazing furnace, the sintering temperature is set to 600°C, and the sintering is carried out in an ammonia decomposition atmosphere, and the high temperature sintering time is maintained for 70 minutes. After the sintering is completed, the sintered body is naturally cooled to room temperature, and the bending strength of the sintered body is tested.

[0093] The relative sintering index was calculated based on the flexural strength of the sintered bodies of the examples and comparative examples.

[0094] Table 1 - Test results of flexural strength and relative sintering index of sintered body

[0095]

[0096]

[0097] It can be seen from Table 1 that the metal fine powder sintering performance test method provided by the present invention can more truly reflect the sintering performance of metal fine powder. The actual sintering performance of copper powders with particle sizes of 1μm, 2μm, and 4μm is very close, which is consistent with the test results of the embodiments of the present invention. However, the bending strength obtained by the tests of comparative examples 1 to 3 is quite different and not in line with reality; this is because when fine-particle copper powder with a small particle size is used alone for sintering, the fine-particle copper powder has poor fluidity, resulting in more sintering defects, and the sintering strength obtained by the test is inaccurate, which cannot truly reflect the sintering performance of the fine-particle copper powder.

[0098] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

[0099] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for testing the sintering performance of metal fine powder, wherein the particle size of the metal fine powder is 0.1 to 10 μm, characterized in that: include: The metal fine powder and the metal coarse powder with a particle size of 30 to 100 μm are mixed in proportion so that the metal fine powder is evenly coated on the outer surface of the metal coarse powder to obtain a mixed powder; The mixed powder and the metal coarse powder are respectively loaded into molds of the same specifications, compacted, and then sintered under the same conditions to obtain a mixed powder sintered body and a metal coarse powder sintered body; The flexural strength A of the mixed powder sintered body and the flexural strength B of the metal coarse powder sintered body are tested, and the relative sintering index A / B of the mixed powder and the metal coarse powder is calculated. The sintering performance of the metal fine powder is characterized by the relative sintering index A / B.

2. The method for testing the sintering performance of metal fine powder according to claim 1, characterized in that: The mass ratio of the metal fine powder to the metal coarse powder is 1:(1-3).

3. The method for testing the sintering performance of metal fine powder according to claim 1, characterized in that: The mixing method of the metal fine powder and the metal coarse powder includes: Mix the metal fine powder and the metal coarse powder, add a wetting agent, and mix well in a mixer.

4. The method for testing the sintering performance of metal fine powder according to claim 3, characterized in that: The wetting agent includes at least one of paraffin, glycerin, and spindle oil.

5. The method for testing the sintering performance of metal fine powder according to claim 3, characterized in that: The amount of the wetting agent added is 0.2-0.5% of the total mass of the metal fine powder and the metal coarse powder.

6. The method for testing the sintering performance of metal fine powder according to claim 1, characterized in that: Before mixing the metal fine powder and the metal coarse powder, the metal coarse powder is plasma treated to increase the surface energy of the metal coarse powder.

7. The method for testing the sintering performance of metal fine powder according to claim 6, characterized in that: The plasma treatment method includes: The metal coarse powder is placed in a plasma reactor, oxygen is used as a plasma source, and the processing time is 3 to 5 minutes under the conditions of an operating pressure of 100 Pa and a radio frequency power of 200 W.

8. The method for testing the sintering performance of metal fine powder according to claim 1, characterized in that: The sintering method of the mixed powder and the metal coarse powder includes: The mold filled with the mixed powder and the metal coarse powder is placed in a sintering furnace and sintered at 600-930°C for 50-80 minutes in a reducing atmosphere or a protective atmosphere.

9. The method for testing the sintering performance of metal fine powder according to claim 8, characterized in that: The reducing atmosphere is a hydrogen atmosphere or an ammonia decomposition atmosphere.

10. The method for testing the sintering performance of metal fine powder according to claim 1, characterized in that: The metal fine powder is a single substance powder such as copper powder or an alloy powder such as steel powder.